MOTIVASI KREATOR INDONESIA PADA GAME ONLINE ZEPETO DALAM MENCIPTAKAN ITEM 3D MELALUI GAME SMARTPHONE - Dinda Ayu; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Game is a game that can be played by all ages. Now with the passage of time, games have had many developments, ranging from traditional to entering the world of the internet that can be accessed offline and online. Many people use games as a form of entertainment in their spare time, even making it a hobby. But some people take advantage of gaming as a positive thing that can benefit players, such as making money just playing games. Then people make gaming their job, because it can make money like any other job. In this study, ZEPETO is one of the many 3D avatar games that can let players have the freedom to decorate their avatars and more. The purpose of this research is to find out who the Indonesian creators are and what is the motivation of the Indonesian ZEPETO creators in creating 3D items through smartphone games. The method used in this research is qualitative with a descriptive approach. The subjects selected in this study were five informants using the snowball sampling technique. The results of this study indicate that there are three points that can be concluded, ZEPETO game players can be free to be creative through content, videos, item creation and maps. Then players can communicate with other players from all over the world, and decorate 3D avatars by creating items that can generate profits for users. Key words: Motivation, Creator, ZEPETO Game, 3D Items.